Pengesampingan Pasal Dalam Perjanjian Oleh Para Pihak Dikaitkan Dengan Asas Kebebasan Berkontrak - Dyah Auliah Rachma Ruslan (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Until now, in the practice of making contracts/agreements, in general, many parties have made waivers of articles in the Civil Code (hereinafter referred to as the Civil Code). In general, the articles that are set aside are Article 1266 of the Civil Code and Article 1267 of the Civil Code.Purposes of the Research: Provide an explanation of the articles in the Civil Code that can be waived and their relation to the principle of freedom of contract. Methods of the Research: The research method used is normative legal research. The main subject of the study is law which is conceptualized as a norm or rule that applies in society and becomes a reference for everyone's behavior.Results of the Research: Referring to the principle of freedom of contract, in making an agreement not only Article 1266 and Article 1267 of the Civil Code can be waived by the parties, but the parties can also waive the articles governing agreements in Book Three of the Civil Code as long as they fulfill the legal requirements of the agreement. and does not harm either party. Because Book Three of the Civil Code which regulates agreements adheres to an open system.